2016
DOI: 10.1080/02571862.2016.1148787
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield responses of commercial sugarcane cultivars to mulching in the coastal rainfed region of South Africa

Abstract: The perceived negative cultivar responses to mulching has limited the adoption of this practice in the South African sugarcane industry. This study was aimed at evaluating cane yield and quality responses and population dynamics of popular cultivars to mulching in the rainfed region of South Africa. A four replicate field trial was established using a strip-plot design. Cane and tons estimated recoverable crystal yields (TERC), and yield components were determined in three summer ratoons and one winter ratoon.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The last observed reductions were of 4 and 15% in the cycle of plant cane and ratoon, respectively. The presence of straw on the soil increased the juice purity, and the remaining other industrial indexes were not negatively affected by the straw (Table 1), as found by Ramburan and Nxumalo (2017), Nxumalo et al (2017), and Aquino et al (2018).…”
Section: Discussionsupporting
confidence: 54%
“…The last observed reductions were of 4 and 15% in the cycle of plant cane and ratoon, respectively. The presence of straw on the soil increased the juice purity, and the remaining other industrial indexes were not negatively affected by the straw (Table 1), as found by Ramburan and Nxumalo (2017), Nxumalo et al (2017), and Aquino et al (2018).…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies, however, have shown variable plant tillering responses to straw cover. Nxumalo et al (2017) reported that delayed plant emergence and early crop establishment due to straw cover did not affect the final plant population compared with straw removal. In contrast, Campos et al (2010) concluded that raking improved plant tillering and final population compared with no raking (i.e., straw cover), particularly for cooler regions of southeastern Brazil.…”
Section: Plant Tillering Response To Straw Managementmentioning
confidence: 98%
“…Intercropping can also help in improving soil microbial diversity (Li et al 2012;Solanki et al 2019) and its activity (Solanki et al 2019), increasing AMF (Zhang et al 2020), as well as providing extra economic benefits to sugarcane growers (Chagas et al 2015;Teshome et al 2015;Ullah et al 2017;Shukla et al 2019;Nadeem et al 2020). Green harvesting and trash blanket  Maintaining or improving soil organic carbon and the other nutrients (Singh et al 2012;Trivelin et al 2013;Shukla et al 2016;Sandhu et al 2017;Luca et al 2018;Castioni et al 2019)  Improving soil physical quality attributes, such as increasing soil waterstable aggregates (Surendran et al 2016) and preventing soil compaction (Castioni et al 2018)  Avoiding sudden fluctuations in soil temperature (Awe et al 2015)  Preserving soil moisture (Liao et al 2013;Nxumalo et al 2016 (Jiang et al 2012;Prado et al 2013;Dotaniya et al 2016;dos Santos et al 2020)  Increasing the abundance of soil biota, including soil microbes (Balota and Auler 2011;Nair and Ngouajio 2012;Neher et al 2013;van Horn et al 2013;Zaccardelli et al 2013;El-Sharouny 2014;Zhen et al 2014;Sun et al 2015;Francioli et al 2016;Spiegel et al 2018;Zhu et al 2020) and fungi (Miura et al 2013;…”
Section: Intercroppingmentioning
confidence: 99%
“…An increased number of earthworms can help in regulating soil structure Frazão et al 2019) and play a role in the soil nutrient cycling process through decomposition and mineralization (Lubbers et al 2010;Bernard et al 2012;Domínguez and Gómez-Brandón 2013;van Groenigen et al 2014;Wachendorf et al 2014;Waqar et al 2019); thus, it leads to reduced fertilizer requirements. Previous studies showed an increase in sugarcane yield due to the implementation of trash blanket (Surendran et al 2016;Singh et al 2012;Liao et al 2013;Ng Cheong and Teeluck 2015;Nxumalo et al 2016;de Aquino et al 2017;de Aquino et al 2018;Dhanapal et al 2018;Corrêa et al 2019). If the trash blanket method is implemented continuously in a sugarcane plantation, beneficial soil biota will create a positive feedback system with continuous soil fertility improvements.…”
Section: Green Harvesting and Trash Blanketmentioning
confidence: 99%